From Awareness to Practice: Indonesian Pre-Service English Teachers’ Perceptions and Implementation of Intercultural Communicative Competence - Mohamad, Raditya; Nurkamto, Joko (Universitas Hamzanwadi, 2025)
Intercultural communicative competence (ICC) is critical in English language education, especially in preparing future teachers to address cultural diversity in the classroom. Despite growing awareness of ICC, challenges remain in how pre-service teachers perceive and plan to implement ICC in their future teaching practices. This study investigated Indonesian pre-service English teachers’ perceptions of ICC objectives and their intended integration into English language instruction. Conducted at a university in Central Java, Indonesia, the study involved 19 undergraduate pre-service English teachers who completed a questionnaire, all of whom were invited to participate in follow-up interviews. The questionnaire responses were analyzed using descriptive statistics, while interview data were examined through thematic analysis. The findings indicate that participants generally acknowledged the importance of ICC, particularly the knowledge dimension—such as understanding non-verbal behaviors, taboos, and levels of formality—and, to a lesser extent, attitudes like suspending judgment. However, responses also revealed inconsistencies, as many participants favored teacher-centered approaches focused on presenting cultural facts, with limited attention to deeper cultural engagement or student-centered activities. Although some participants demonstrated more comprehensive and reflective approaches, the findings suggest that many pre-service teachers have a fragmented understanding of ICC and lack clear strategies for its classroom integration. These results highlight the need for teacher education programs to explicitly address ICC objectives, foster critical intercultural awareness, and promote reflective pedagogies that support effective ICC implementation in future English language classrooms.